Computer games as cultural heritage - Garda, Maria B. (Replay. The Polish Journal of Game Studies, 2014)
The aim of the article is to discuss the challenges of computer games preservation as a cultural heritage, focusing on the Polish perspective. Computer games are predominantly perceived as ‘new media’, despite the fact that their history dates back to the mid-20th century. It is important to understand that not only the early computer games are already ‘old media’ but all the digital games are. They may be perceived as ‘dying media’ vulnerable to unprecedented obsolescence. The article explores the consequences of digital decay and the notion of original experience in the context of conservation strategies. It suggests that there is still a need for a more conscious inclusion of computer games within the agenda of the Polish heritage institutions.